Volume 3B: General 1993
DOI: 10.1115/93-gt-259
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Analysis of the Flow in the Impeller Rear Cavity of Aeroengines

Abstract: A 3-D Navier-Stokes CFD code has been applied to analyze the complicated viscous driven flow in the centrifugal compressor impeller rear cavity of aeroengines. The caculation is compared with measurements. Three different configurations are analyzed. For each case the computed flow details provide valuable information for optimizing the engine design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For the swirl nozzle flow (Liu et al, 1995), excellent agreement between the calculation and the measurement was obtained. For the impeller rear cavity flow calculation (Liu et al,1993), fair agreement with measurement was found. However.…”
Section: The Calculation Methodsmentioning
confidence: 71%
“…For the swirl nozzle flow (Liu et al, 1995), excellent agreement between the calculation and the measurement was obtained. For the impeller rear cavity flow calculation (Liu et al,1993), fair agreement with measurement was found. However.…”
Section: The Calculation Methodsmentioning
confidence: 71%
“…Hence an understanding of the variation in static pressure distribution as bleed air is passed through the impeller rear face cavity is of extreme importance to the design of the internal air system of the engine. This may be achieved for each particular design case by the use of component test rigs or detailed CFD analysis such as that performed by Liu and Patel (1993). However, there is a need in industry for simpler but adequate analysis methods that can be used frequently in the parametric studies associated with the preliminary design process.…”
Section: Figure 1 Typical Impeller Rear Face Rotor-stator Cavity Confmentioning
confidence: 99%
“…A considerable amount of work about the flow characteristics in the rotor-stator cavity with a centripetal inflow has been carried out by a number of workers [1][2][3][4][5][6]. The results show that for a rotor-stator cavity with centripetal flow, the internal flow conforms to the Batchelor type which consisted of an inviscid core and two Ekman type boundary layers.…”
Section: Introductionmentioning
confidence: 99%